Grading requirements for a coarse- aggregate with a maximum nominal size of 16 mm - Rojas, Einer Rodríguez (2023)
In Costa Rica, the most widely used standard in terms of specifications to assess the quality of aggregates for hydraulic concrete corresponds to that of the American Society for Testing and Materials (ASTM), which constitutes the basis for of the standards of the Institute of Technical Standards of Costa Rica (INTECO). Therefore, the graduation requirements of the aggregates that are followed in the country come from the ASTM C33 standard Specification for aggregates for concrete (INTE C15:2014). For mix design, this standard provides grading specifications for nominal maximum sizes of 90 mm, 63 mm, 50 mm, 37,5 mm, 25 mm, 19 mm, 12,7mm and 9,5 mm. However, in recent studies, Hernández (2018) and Delgado (2018), used an aggregate with a nominal maximum size of 16 mm in the production of hydraulic concrete to obtain standard resistance development curves for different types of portland cement that are marketed in the country. In their work, both Hernández and Delgado used coarse river aggregate and coarse pit aggregate. For each case, the specifications for maximum nominal sizes of 12,7 mm and 19 mm provided by the ASTM C33 (INTE C15:2014) standard were used as granulometric reference, since in this standard there are no specifications for aggregate of 16 mm. Aggregate-producing sources at the national level are generating a significant amount of 16 mm aggregate, so it was interesting to carry out an experimental study with statistically valid samples, which allow verifying with an adequate degree of certainty the validity of using the granulometry that best will fit (nominal maximum size: 12,7mm or 19 mm) when using 16 mm aggregate. But also, as part of the study, a proposal for granulometric limits was generated for a size of 16 mm.